Caught on camera: Teachers' surveillance in schools. (February 2019) - Perry-Hazan, Lotem; Birnhack, Michael
Abstract: This study explores the surveillance of Israeli teachers by CCTV systems (CCTVs), based on interviews with teachers who reported being monitored by CCTVs in their schools and with school principals using CCTVs to monitor teachers. The findings present and analyze forms of teachers' CCTV surveillance, its impact on teachers' behavior, their feelings, and their normative perceptions. We find that teachers' surveillance by CCTVs includes spatial and temporal dimensions that differ from other forms of teachers' monitoring. The findings show how surveillance demoralizes teachers, induces resistance, and produces social categorizations that exacerbate teachers' low social status. Highlights: Teachers' surveillance by CCTVs carries with it new spatial and temporal dimensions. These dimensions modify the structure, background rules, and power relationships between teachers and principals. Some teachers resisted the surveillance by performing, avoiding, concealing, and by initiating a grievance discourse. Even teachers who felt distress regarding their own surveillance justified the surveillance of other teachers. Teachers' surveillance produces social categorizations that exacerbate teachers' low social status.